2005
DOI: 10.5144/0256-4947.2005.29
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism in north India: a description of 52 cases

Abstract: BACKGROUNDPrimary hyperparathyroidism (PHPT) has a variable clinical expression. Symptomatic PHPT is still the predominant form of the disease in many parts of the world, especially developing countries. Because the clinical profile of the disease has changed from that described in the past, we sought to improve our understanding of the disease in patients in north India.METHODSWe summarized the clinical presentation, biochemical and radiological features, and operative findings from the case records from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
85
9
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 25 publications
15
85
9
1
Order By: Relevance
“…The major clinical manifestation in our patient group was bone pain and more than half of our patients had bone involvement. Our previous study (24) and a recent publication from China (28) have also shown that PHPT is still symptomatic with bone manifestations in this part of the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major clinical manifestation in our patient group was bone pain and more than half of our patients had bone involvement. Our previous study (24) and a recent publication from China (28) have also shown that PHPT is still symptomatic with bone manifestations in this part of the world.…”
Section: Discussionmentioning
confidence: 99%
“…unlike the mostly asymptomatic nature of presentation in the West (24). Accordingly, we examined the expression of VDR, CASR, CD1, and PTH using immunohistochemistry and confirmed with mRNA analyses in a cohort of parathyroid adenomas from Asian Indian patients with symptomatic PHPT.…”
Section: Presentation Of Phpt In Asian Indian Is Symptomaticmentioning
confidence: 99%
See 1 more Smart Citation
“…Technetium-99 pertechnetate subtraction has been reported to have a sensitivity of 87-100% [12,14,15] . Contrast-enhanced computerized tomography (CECT) of the neck has a sensitivity ranging from 65% to 93.5% in localizing parathyroid adenoma [12,13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Neck ultrasound (USG) has been reported to localize the adenoma in 65-77% of patients [12,13,14] . Methyl isobutyl isonitrile (MIBI) scan positivity has been reported in 86.9-100% [14,15] .…”
Section: Discussionmentioning
confidence: 99%